Pengaruh Media Video terhadap Minat Belajar Siswa Kelas V dalam Pendidikan Agama Katolik di SD Negeri 076689 Fulolo Alasa - Yulianus Hulu; Yoseph Kristianto; Agustina Susi Indratni (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to see the effect of video media on the students’ learning interests for the fifth grade students in the learning process of Catholic religious education. Video media is one of the teacher's aids, which can be used as a bridge from the teachers and students in teaching and learning process The video is displaying the learning materials about Catholic religious education. This is quantitative research with experiment design. The population in this study were students of the fifth-grade in SD Negeri 076689 Fulolo Alasa elementary school. The samples are the class of V as a control as an experiment class. The researcher does a raffle from five classes to get the sample. Data collection techniques in this study were carried out by observation, questionnaire and student learning outcomes in class V.